2011
DOI: 10.1002/pc.22148
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nanosilica on styrene free radical polymerization kinetics

Abstract: A series of nanocomposites were prepared by in situ polymerization of styrene with different silica content (1, 3, and 5 wt%) with an average particle size of 7 nm. The influence of nanosilica content on the kinetics of styrene free radical bulk polymerization was studied by isothermal differential scanning calorimetry (DSC) at different temperatures (70, 80, and 908C). Using appropriate kinetic model, describing two reactions observed during styrene polymerization (the first-order reaction and autoacceleratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The heat release after t 0 is most probably caused by the initiator decomposition and the formation of free radicals. In our previous research, the induction period during styrene polymerization was not observed . For the further investigation of polymerization kinetics, it is necessary to transform isothermal DSC data, in order to describe only the polymerization reaction without induction time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The heat release after t 0 is most probably caused by the initiator decomposition and the formation of free radicals. In our previous research, the induction period during styrene polymerization was not observed . For the further investigation of polymerization kinetics, it is necessary to transform isothermal DSC data, in order to describe only the polymerization reaction without induction time.…”
Section: Resultsmentioning
confidence: 99%
“…Polymerizations were performed under isothermal conditions at 70°C. The amount of polymerized monomer (proportional to the heat released during the reaction) was calculated from the area between the isothermal DSC curve and the baseline using the method described in the literature . The amount of unreacted monomer was determined by prolonging the polymerization in the dynamic regime, from the temperature of isothermal polymerization to 220°C, at a heating rate of 10°C min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations